Effect of particle doping on the mechanical behavior of 2D woven (0 ∘ /90 ∘) jute fabric (plain weave) reinforced polymer matrix composites - Singh V.; Kumar P.; Srivastava V.K. (My University, 2025)
The performance and functionality of natural fiber reinforced polymer composites can be enhanced many folds by incorporating hard filler particulates which may significantly increase mechanical properties. This study was aimed to hybridize the jute fabric reinforced polymer (JFRP) based laminated composites with cement particulates for the enhancement of their mechanical properties. The laminated cement particulates filled jute fabric reinforced polymer (CmJFRP) and JFRP composites were fabricated via hand lay-up method. The weight fraction of cement particles was varied as 1%, 3%, and 5%. The thickness of the composites was also varied as 3.1 mm, 4.4 mm, and 6.3 mm (i.e. by varying the number of lamina). The mechanical behavior of the composites was assessed via tensile test, microhardness, Izod impact test, and critical buckling load. The tensile tests revealed that CmJFRP composites exhibit lower tensile strength than that of JFRP composites, which was mainly ascribed to the agglomeration of cement particles at the fiber/matrix interface. The microhardness, impact strength, and critical buckling load were higher for CmJFRP composites as compared to JFRP composites. The scanning electron microscopy of the fractured composites revealed that crack front changed its plane and direction when it encountered the cement particles. © 2022, Indian Academy of Sciences.